Combustion-based power source for Venus surface missions. (October 2016) - Miller, Timothy F.; Paul, Michael V.; Oleson, Steven R.
Abstract: The National Research Council has identified in situ exploration of Venus as an important mission for the coming decade of NASA's exploration of our solar system (Squyers, 2013[1] ). Heavy cloud cover makes the use of solar photovoltaics extremely problematic for power generation for Venus surface missions. In this paper, we propose a class of planetary exploration missions (for use on Venus and elsewhere) in solar-deprived situations where photovoltaics cannot be used, batteries do not provide sufficient specific energy and mission duration, and nuclear systems may be too costly or complex to justify or simply unavailable. Metal-fueled, combustion-based powerplants have been demonstrated for application in the terrestrial undersea environment. Modified or extended versions of the undersea-based systems may be appropriate for these sunless missions. We describe systems carrying lithium fuel and sulfur-hexafluoride oxidizer that have the potential for many days of operation in the sunless craters of the moon. On Venus a system level specific energy of 240 to 370 We -hr/kg should be possible if the oxidizer is brought from earth. By using either lithium or a magnesium-based alloy fuel, it may be possible to operate a similar system with CO2 derived directly from the Venus atmosphere, thus providing an estimated system specific energy of 1100 We+PV -hr/kg (the subscript refers to both electrical and mechanical power), thereby providing mission durations that enable useful scientific investigation. The results of an analysis performed by the NASA Glenn COMPASS team describe a mission operating at 2.3 kWe+PV for 5 days (120 h), with less than 260 kg power/energy system mass total. This lander would be of a size and cost suitable for a New Frontiers class of mission. Highlights: A Venus heat engine that burns Li with atmospheric CO2 is proposed. It would achieve system specific energy 2.8–3.7 times high temperature batteries. All reaction products would remain on board the lander. Operation at 2.3 kWe+PV for 5 days with 260 kg energy system mass is described. This lander would have size and cost suitable for a New Frontiers class mission.